(untitled) (Actualité en allergologie et en immunologie au Canada, 2023)
Pruritus is a common symptom that all individuals have experienced at some time. Although general malignancy is a rare cause of pruritus, there is an increased risk of hematologic malignancy in those with chronic itch. For the allergist assessing chronic itch, we have outlined an approach in the case of suspected hematologic malignancy and steps for an initial work-up.